Bellfry - Ghosh, Ayan (2023)
As the tallest structure in Fort, St. Thomas Cathedral once acted as a visual landmark. Over the years, the spire was remodeled to make it look more Gothic. It houses a belfry and clock tower. Though the bells are no longer operational, they are still in the spire, where they were installed in 1798. The clocks, however, are still operational.